2015
DOI: 10.3928/00989134-20141014-02
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Therapeutic Techniques to Decrease Agitation in Geriatric Psychiatric Patients With Dementia

Abstract: Agitation is not only a frequent and disturbing behavior for many patients with dementia, but it also troubles their caregivers and families. Many serious problems and side effects are associated with the use of medications to treat agitation; therefore, alternative approaches to treating agitation must be assessed. The current article presents results from a quality improvement pilot project that examined the usefulness of a specially designed, multisensory room intervention for geriatric psychiatric inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Interventions directly targeting the symptoms of disorientation and/or derealization that increase the risk of disruptive behaviors among patients suffering from cognitive impairments might be interesting and promising alternatives. For example, architectural changes in wards, such as multisensory rooms or senses-based interventions, including Snoezelen therapy or a "controlled multisensory environment," aimed at alleviating the symptoms of disorientation and/or derealization through sensory stimuli seem promising [63,64]. Including a patient's relatives in clinical discussions and decisions is also an alternative for the care of patients with cognitive impairments [61,65].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Interventions directly targeting the symptoms of disorientation and/or derealization that increase the risk of disruptive behaviors among patients suffering from cognitive impairments might be interesting and promising alternatives. For example, architectural changes in wards, such as multisensory rooms or senses-based interventions, including Snoezelen therapy or a "controlled multisensory environment," aimed at alleviating the symptoms of disorientation and/or derealization through sensory stimuli seem promising [63,64]. Including a patient's relatives in clinical discussions and decisions is also an alternative for the care of patients with cognitive impairments [61,65].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Mitchell, Chiappetta (17) This article presents results from a quality improvement pilot project that examined the usefulness of a specially designed, multisensory room intervention which included music for inpatients in a psycho-geriatric treatment facility who had mild to moderate agitation. They found that using the multi-sensory room decreased agitation as measured by the Pittsburgh Agitation Scale (PAS) for up to an hour in all sub-scales with the exception the aggression subscale.…”
Section: Authorsmentioning
confidence: 99%
“…Alternatively, non-pharmacological treatment is based on high levels of patient and caregiver satisfaction, and reduced behavioural symptoms with minimal risk and adverse reactions (14,15). The most common non-pharmacological therapies are music therapy, aromatherapy and massage, laughter, structured activities, animal-assisted interventions, environmental interventions, simulated presence, dance movement, art, and combination therapies (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the reviewed articles focused on non-pharmacological interventions, it is noted that both pharmacological and non-pharmacological interventions are widely used concurrently in many healthcare facilities [3]. While pharmacological interventions are undoubtedly needed in some cases, the benefit of decreasing the risk of serious adverse drug effects is noted related to the use of nonpharmacological interventions [8]. A complementary pharmacological intervention would include frequent medication reviews to reduce the administration of unnecessary and inappropriate medications [9].…”
Section: Strengths and Limitations Of Selected Referencesmentioning
confidence: 99%